ENHANCE CONTROLLING TEXT INFORMATION TECHNICAL BASED ON ARDUINO UNO ATMEGA 2560 - Fahrurrozi lubis (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
Running Text is an alternative information media its be used by the public because of affordable price and attractive appearance. Along with the times, to change the information in the current text can be done in various ways one of them online (internet). But the results of previous studies still leave a problem, namely the number of characters that can be stored is only 30 characters with a duration of change of 15 seconds and can only display the characters perfectly as many as 5 repetitions for subsequent running text will be an error. Based on the problems mentioned above, the purpose of this study is to design text that runs online that can store up to more than 50 characters and find out the cause of errors that occurred in previous studies. In this paper used in the demonstration application of the results of trials that have been carried out is known that the text running online designed this study can accommodate more than 60 characters and errors that occur in the text running the previous study because the capacity of the Arduino uno 328 RAM is not suitable for operation The text goes online.